Capital Flows in the APEC Region - Reinhart, Carmen; Khan, Mohsin (Washington, D.C. : International Monetary Fund, 1995)
The developing economies of the Asia Pacific Economic Cooperation (APEC) have been the recipients of a considerable volume of capital inflows in the 1990s. Given the increased integration of capital markets, it is not surprising that monetary control became more difficult for many developing APEC economies. Formulating an appropriate policy response has naturally been important. The three papers that make up this Occasional Paper each examine different aspects of these issues.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet